Reconhecimento de padrões através de análises estatísticas e fractais aplicadas a dados de ensaios não-destrutivos - Silva, Francisco Estênio da (2011)
In this work a procedure is studied for pattern classification related to different types of data, namely: (1) signals obtained from ultrasonic testing ( pulse-echo technique) and magnetic signals obtained from Barkhäusen noise in samples of ferritic-pearlitic carbon steel tubes which, due to temperature effects, have shown microstructural changes as consequence of the total or partial transformation of the pearlite into spherodite; (2) images built from TOFD ultrasonic testing and 8 bit digital radiographic images obtained from carbon steel 1020 sheets, with different welding defects. From the data obtained, images have been considered with the defects as lack of fusion, lack of penetration, porosity and images without defect. For this aim, non-conventional mathematical techniques have been used for the preprocessing of the data, namely, the statistical analyses, Hurst analysis (RSA) and detrended fluctuation analysis (DFA), and fractal analyses, box counting analysis (BCA) and minimal cover analysis (MCA). The curves obtained with the initial mathematical treatment, discrete functions of the temporal window width, have been handled with the supervised and nonsupervised pattern recognition techniques known as principal component analysis and Karhunen-Loève (KL) transformation analysis respectively. With respect to the magnetic signals, the KL classifier has been shown to be very efficient when applied to DFA obtained from the magnetic flux, with a success rate around 94%. On the other hand, for the magnetic noise signals we have not obtained an acceptable success rate independently of the preprocessing used. However, when were considered the curves obtained by concatenating all curves of the pre-processing was obtained a consistent average success rate of 85%. As far as the rate of success of the PCA classifier is concerned, an excellent success of 96% has been reached for concatenated curves of selected data of magnetic noise only. As far as the analyses of the backscattered ultrasonic signals is concerned, it was not possible to classify the different stages of the microstructural degradation by using KL or PCA independently of the pre-processing used. As far as the analyses of the D-scan images are concerned, by applying PCA a rate of success of 81% has been obtained with MCA data, 73% has been obtained by concatenating all curves from the different fractal and statistical analyses and around 85% when concatenating the best individual results (DFA and MCA). On the other hand, considering the KL classifier, high success rates have been verified for the training stage, between 96% and 99%, and a maximum success rate (100%), when concatenating all analyses. With respect to the testing results, the best success rate which has been reached was approximately 77%, when concatenating all the curves obtained from the statistical and fractal pre-processing. For the digitalized radiographic images, relevant individual rates of success (between 70% and 90%) for the training set (consisting of all data) have been obtained for the classifier KL only, and a 100% success rate, when concatenating all the curves obtained from the pre-processing of the images.